2013
DOI: 10.1080/01629778.2013.853199
|View full text |Cite
|
Sign up to set email alerts
|

Riga City Youth between Latvian and Russian

Abstract: This paper presents the findings of a survey of 995 late adolescent residents of Riga -Lettophones, Russophones, and native bilinguals -offering evidence that the youngest generation of Latvia's capital has broken away from Soviet-era language trends, communicating in Latvian more frequently and confidently than Russian. Two correspondences, unique to the linguistic group in question, are also discussed. (1) Among the Lettophones, any preference for the other language in intercultural communication is far more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…More specifically, young Russian speakers are increasingly able to decouple from their compatriots in Russia and approach the perceptions of Latvian speakers (Cheskin, 2013b, 23–24). Breggin (2014: 178) evaluated the use of language among youth in Riga. He concluded that breaking up with the Soviet‐era modes of interaction is indisputable as the Latvian language dominates communication among the youth of different ethnic backgrounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, young Russian speakers are increasingly able to decouple from their compatriots in Russia and approach the perceptions of Latvian speakers (Cheskin, 2013b, 23–24). Breggin (2014: 178) evaluated the use of language among youth in Riga. He concluded that breaking up with the Soviet‐era modes of interaction is indisputable as the Latvian language dominates communication among the youth of different ethnic backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…He concluded that breaking up with the Soviet‐era modes of interaction is indisputable as the Latvian language dominates communication among the youth of different ethnic backgrounds. He noted that Russian is still used vibrantly for intercultural interaction (Breggin, 2014: 178).…”
Section: Introductionmentioning
confidence: 99%